Effect of Culture on Gender Differences in Risky Driver Behavior through Comparative Analysis of 32 Countries. Issue 3 (March 2021) - Granié, Marie-Axelle; Thévenet, Chloé; Varet, Florent; Evennou, Myriam; Oulid-Azouz, Noureddine; Lyon, Craig; Meesmann, Uta; Robertson, Robyn; Torfs, Katrien; Vanlaar, Ward; Woods-Fry, Heather; Van den Berghe, Wouter
This study examines the effect of culture on gender differences in road user risky behaviors. With the hypothesis that gender differences are not solely because of biological factors, and that the existence and magnitude of differences between gender groups vary according to cultural context, because of differentiated social expectations in relation to gender roles, a secondary analysis was made of the E-Survey of Road Users' Attitudes (ESRA) 2018 database, comprising 25, 459 car drivers (53% male) surveyed by an online questionnaire in 32 countries distributed in eight cultural clusters. The interactions between gender and culture in reported behavior, and personal and social acceptability of four violations were analyzed: drinking and driving, speeding, not wearing a seatbelt, and the use of a cellphone while driving. The results show significant gender differences on risky behaviors and attitudes and complex interactions between gender and culture, with men valuing crash-risk behaviors more than women do in all cultural clusters observed. Interactions between gender and culture are more frequent on declared behaviors and personal acceptability than on perceived social acceptability, and on drinking and driving, and not wearing a seatbelt, more than on speeding and the use of a cellphone while driving. In addition, gender differences are greater in Western countries than in the Global South. These gender differences in road user behaviors, attitudes, and perceptions as results of an interaction between biological and evolutionary factors and cultural and social factors are discussed. These results could be useful to better tailor road safety campaigns and education.